THE ROLE OF LAW IN ECONOMIC GLOBALIZATION IN INDONESIA - Ukas Ukas; Zuhdi Arman (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2020)
Legal development has a more comprehensive and basic meaning compared to the promotion and renewal of law in the context of increasing the nation's competitiveness, legal politics in Indonesia directs legal development to encourage economic growth. The research objective is to determine economic growth, especially in the business world and in the industrial world which determines investment capacity, especially law enforcement and protection. The method used is normative juridical. The results of this study see Law as a social engineering tool that was born because the concept of law is taught to direct people to better understand change. Law as an instrument of development control includes development in the economic field. Enforcement of law and justice in particular in the economic development of activities and developing development in accordance with long-term government programs. The role of law in economic globalization in the 21st century is certainly expected aspects of globalization in legal and economic growth, the development of economic law also includes investment law, which of course must run in accordance with long-term development tools.